The Influence of Training and Education (Diklat) and Service Period on Personnel Career Development in The Special Detacion 88 Anti-Terror of The Police of The Republic of Indonesia - Hari Priyanto; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti International Journal of Management Science, 2026)
The research objectives are as follows: To analyze and test the influence of education and training (Diklat) on personnel career development, Analyze and test the influence of length of service on personnel career development and Analyze and test simultaneously the effects of education and training (Training) and length of service on personnel career development, for the Education Training (Diklat) variable (X1) of 6,838 while the t-table value for n = 130 is 1.978. So 6.838 > 1.978 , then H0 is rejected and Ha is accepted, it can be stated that Education and Training (Diklat) (X1) has a significant effect on personnel career development (Y), the calculated t value for the variable Length of Service (X2) is 6.402, while the ttable value for n = 130 is 1.978. So 6.402 > 1.978, then H0 is rejected and Ha is accepted, it can be concluded that partially the variable Length of Service (X2) has an effect on personnel career development (Y) and the test ANOVA obtained a calculated F value of 111.456, while the Ftable (0.05 a) for n = 130 was 2.67. So the calculated F > from the Ftable (a 0.05) or 111.456 > 2.67 with a significance level of 0.000 because 0.000 < 0.05, it can be said that Education and Training (Diklat) (X1) and Service Period (X2) together or simultaneously have a positive effect on personnel career development (Y).